Frozen semen quality and fertility of imported pure Holstein Friesian and Sahiwal breeding bulls in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
The present study was conducted to evaluate the frozen semen quality in terms of different motility patterns and fertility of imported pure Holstein Friesian and Sahiwal breeding bulls maintained under farming condition of Bangladesh. 100% pure Holstein Friesian and Sahiwal breeding bulls were imported and thereafter reared in the American dairy limited (ADL). Semen samples were collected once a week, processed and frozen in the laboratory of ADL. On the day of collection, semen volume and sperm concentration measured immediately after collection. Different motility patterns of spermatozoa (progressive, fast, slow, local, immotile) were measured by Computer Assisted Semen Analyzer (CASA). Effect of breed was found significant (p